Kompensasi Dan Dukungan Organisasi terhadap Ketertarikan Pelamar Kerja: Efektifitas Pemberian Informasi - Dany Fajar Setiawan; Erika Setyanti Kusumaputri (Universitas Islam Indonesia, 2017)
This research was purposed to find out the effect of company profile booklet based on compensation and company profile booklet based on organizational support toward applicants attractiveness. Furthermore, this research alsofind out which company profile booklet that has more attractiveness between company profile based on compensation or company profile booklet based on organizational support. The subjects in this research were 60 students in last term who study in Yogyakarta. The data were collected through random sampling technique. Themethod of this research was ‘post test only’ experiment design and using attractiveness scale. Then, this reseacrh was analized using comparison test, Mann Whitney U analysis teqnique. The hypothesis was accepted if this research had significant score p < 0,05 , and the significant score of this research was 0,021, where company profile booklet based on organizational support had higher mean rank score which is 35,70%, meanwhile the mean rank score of company profile based on compensation was 25,30%. It also emphasized that company profile booklet based on organizational support more increase the attractiveness for applicants than company profile booklet based on compensation, and it proves that the hypothesis in this research was accepted.Key Words: Attractiveness, Compensation, Organizational Support